Т. 3 - Вейнберг П. И. Петр Исаевич; Миллер Ф. Б.; Кронеберг А. И.; Гербель Н. В.; Дружинин А. В. Александр Васильевич; Холодковский Н. А. Николай Александрович; Михаловский Д. Л. (1888, 1888)
Текст в русской дореформенной орфографии